Improving Conceptual Understanding Through STEM-Based Mathematics Learning - Tonra, Wilda Syam; Syam Tonra, Winda; Ikhsan, Muhammad; Achmad, Fatoni (Universitas Muhammadiyah Mataram, 2022)
This study aims to improve conceptual understanding through STEM-based mathematics learning. The research method was pre-experimental research with one-group pretest-posttest design. The population is grade 8 of one of school in Ternate City. The method of sampling is random sampling. Research variable in the research, the independent variable is STEM-based learning and the dependent variable is the conceptual understanding. The validity of test that will be used in this research is content validity. Data analysis technique are descriptive and inferential. A test given to measure conceptual understanding The indicators are (1) restating a concept and providing examples, (2) Implementing specific procedures or operations, (3) Use algorithm to solve a problem. The results of the study is that students’ conceptual understanding is improving of the circle concept through STEM-based mathematics learning. The increase of conceptual understanding can be seen in the average value obtained, where for the pretest it is 40.41 then after the STEM is applied and the posttest is carried out the average value has increased to 83.73. Therefore, STEM-based mathematics learning is one of approaches that can improve conceptual understanding, and promotes the use of hands-on activities to solve problems in everyday life